Role of fine needle aspiration cytology in primary tubercular epididymo-orchitis - Arghya Bandyopadhyay; Subhadip Khatua; Kousik Bose; Nikhilesh Dewasi (Wolters Kluwer Medknow Publications, 2015)
Tubercular epididymo-orchitis in not uncommon in a highly tuberculosis-prevalent developing country like India. However, it closely mimics a testicular tumor clinically, radiologically, and even serologically. This may lead to an unnecessary orchidectomy. Nevertheless, fine needle aspiration cytology can provide adequate material for cytological and microbiological examination and it helps to avoid unnecessary orchidectomy when there is suspicion of a testicular tumor.